2020
DOI: 10.24042/djm.v3i2.5728
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Errors in Mathematical Problem-Solving Ability on the Triangular and Quadrilateral Materials at Junior High Schools (SMP) Jakarta

Abstract: This research was aimed to analyze student's errors on triangular and quadrilateral material in terms of problem-solving ability. This research was motivated by the low problem-solving ability and errors often made by students during the mathematics learning. The research approach was descriptive-qualitative that was done by analyzing the students' difficulty in solving description problems. The techniques of data collection were observation, learning outcomes tests, and interviews. The data were analyzed qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Problem-solving ability is an important concept that students must understand when learning mathematics (Amalia & Hadi, 2021). The most important goal in learning mathematics is the ability to solve problems (Asriyani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Problem-solving ability is an important concept that students must understand when learning mathematics (Amalia & Hadi, 2021). The most important goal in learning mathematics is the ability to solve problems (Asriyani et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, students have not been able to explain why they choose symbols contained in mathematical equations or models. The research conducted by Asriyani et al (2020) concluded that student errors are caused by: haste to read and understand problems, lack of rigor in the calculation process, and lack of understanding of basic concepts of calculations, algebra, calculation, and fractional reduction. explained students' errors in solving math word problems based on PISA frameworks.…”
Section: Introductionmentioning
confidence: 99%